Glycated albumin activates NADPH oxidase in rat mesangial cells through up-regulation of p47phox - Li, Yanzhang (2010)
Glycated albumin, an early-glycation Amadori-modified protein, stimulates transforming growth factor- β (TGF-β) expression and increases the production of the extracellular matrix proteins in mesangial cells, contributing to the pathogenesis of diabetic nephropathy. Glycated albumin has been shown to increase NADPH oxidase-dependent superoxide formation in mesangial cells. However, the mechanisms are not well understood. Therefore, in the present studies, we determined the mechanisms by which glycated albumin activates NADPH oxidase in primary rat mesangial cells and its contribution to glycated albumin-induced TGF-β expression and extracellular matrix protein production. Our data showed that glyated albumin treatment stimulated NADPH oxidase activity and increased the formation of superoxide formation in rat mesangial cells. Moreover, glycated albumin treatment stimulated the expression and phosphorylation of p47phox, one of the cytosolic regulatory subunits of the NADPH oxidase. However, the levels of other NADPH oxidase subunits including Nox1, Nox 2, Nox4, p22phox, and p67phox were not altered by glycated albumin. Moreover, siRNA-mediated knockdown of p47phox inhibited glycated albumin-induced NADPH oxidase activity and superoxide formation. Glycated albumin-induced TGF-β expression and extracellular matrix production (fibronectin) was also inhibited by p47phox knock down. Taken together, these data suggest that up-regulation of p47phox is involved in glycated albumin mediated activation of NADPH oxidase, leading to glycated albumin-induced expression of TGF-β and extracellular matrix proteins in mesangial cells and contributing to the development of diabetic nephropathy.